Juri Desain Poster dan Fotografi Dalam Rangka Perayaan Mid Auntumn Festival - Evelyn Wijaya; Johan Johan; Teddy Chandra; Stefani Chandra; Martha Martha (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This community service activity was organized by Permatadhis Pelita Indonesia in order to celebrate the moon cake festival or better known as the mid autumn festival, with the theme